PENGARUH TIPE KEPEMILIKAN TERHADAP PROFITABILITAS PERUSAHAAN: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Fransiska Soejono (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
This research is aimed to test the difference in financial performance between firms with various types of ownership (foreign, state, and private) on a sample of 206 firms listed in BEI between 1999-2006 period resulting 795 firm-year observations. ANCOVA model and multiple comparisons are used to test the hypothesis that private-owned firms have better financial performance than state-owned firms and foreign-owned firms have better financial performance than private-owned firms. Contrary with the hypothesis, the result shows that state-owned firms have a better financial performance than private-owned firms. The result also shows that foreign-owned firms have better financial performance than private-owned firms which support the hypothesis. There are some implications of these results. First, different type of ownership give different effect to firm’s financial performance. Second, government can consider foreign ownership in its privatization policy.